2021
DOI: 10.3390/molecules26113147
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic Acid Combined with Melatonin Mitigates Oxidative Stress and Promotes Root Formation and Growth in Salt-Stressed Canola Seedlings (Brassica napus L.)

Abstract: Lipoic acid (LA) and melatonin (MT) are pleiotropic molecules participating in plant stress resistance by modulating cellular biochemical changes, ion homeostasis, and antioxidant enzyme activities. However, the combined role of these two molecules in counteracting the detrimental impacts of salinity stress is still unknown. In the present study, we determined the effects of exogenous LA (0.5 µM), MT (1 µM) and their combination (LA + MT) on growth performance and biomass accumulation, photosynthetic pigments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 53 publications
6
25
0
Order By: Relevance
“…Variety 8046 has shown better performance in relation to plant growth attributes as compared to 7126, as plant height and root length were maximum in 8046 and minimum in 7126 (Table 1). The impact of heat stress-induced damages is cultivar-specific depending on the extent of tolerance based on various tolerance mechanisms including the cellular oxidative defenses in terms of the enzymatic and nonenzymatic antioxidant compounds [58][59][60]. The endogenous content of photosynthetic pigments with CO 2 assimilation rate was also affected in heat susceptible variety (7126) as compared to heat resistant variety (8046), which is in line with the findings of [61].…”
Section: Discussionsupporting
confidence: 77%
“…Variety 8046 has shown better performance in relation to plant growth attributes as compared to 7126, as plant height and root length were maximum in 8046 and minimum in 7126 (Table 1). The impact of heat stress-induced damages is cultivar-specific depending on the extent of tolerance based on various tolerance mechanisms including the cellular oxidative defenses in terms of the enzymatic and nonenzymatic antioxidant compounds [58][59][60]. The endogenous content of photosynthetic pigments with CO 2 assimilation rate was also affected in heat susceptible variety (7126) as compared to heat resistant variety (8046), which is in line with the findings of [61].…”
Section: Discussionsupporting
confidence: 77%
“…Alpha-lipoic acid is a potent antioxidant that is soluble in both water and lipids [44]. A previous report showed that ALA can enhance growth and root formation of the salt-stressed canola seedlings [23]. This stimulation may be due to enhanced photosynthesis and carbon fixation [24].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, ALA-treated plants showed a significant enhancement in their MSI, as well as a parallel decrease in H 2 O 2 and MDA. It has been found that exogenous ALA is a potent dithiol antioxidant and can mitigate oxidative damage by scavenging ROS that are produced under diverse environmental stresses, such as high salinity [23], drought [24], heavy metals [21,25], and osmotic stress [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin ( N -acetyl-5-methoxytrytamine, MT) is a familiar pleiotropic signaling molecule that plays a role as an antioxidant by fostering plant tolerance to various biotic and abiotic stresses [ 15 , 16 ]. MT stimulates various physiological, morphological, and biochemical features starting from seed germination to biological yield [ 17 , 18 ] by the upregulation of stress-related genes [ 17 , 19 ] that scavenge ROS and improve the antioxidant capacity of plants against abiotic stress [ 16 , 20 ]. However, despite numerous research studies, the protective effect of MT against HM stress has not been thoroughly reviewed.…”
Section: Introductionmentioning
confidence: 99%